TECHNOLOGY AND EFFICIENCY IN USAGE OF BROWN COAL ASH FOR CEMENT AND CONCRETE MIXTURES AT THE LELCHITSKY DEPOSIT - G. D. Lyahevich; I. I. Lishtvan; A. G. Lyahevich; V. M. Dudarchik; V. M. Kraiko; S. A. Zvonnik (Наука и техника)
Modern visions on the role of high-dispersity additives in concrete mixtures reflect a positive effect of optimal amount of ash left after combustion of solid fuel on structure and physico-mechanical characteristics of cement compositions: hardening of contact zone between cement stone and aggregates with formation of “binder – aggregate” clusters due to high surface energy of aggregate particles; reduction of total cement stone porosity in concrete while increasing volumetric concentration and aggregate dispersion; binding of calcium hydroxide by amorphized silicon of pozzolanic aggregates; increase in pozzolanic aggregate activity with its fine grinding, etc. Experimental investigations have ascertained that usage of portland cement clinker ash samples left after brown coal burning at the Lelchitsky deposit contributed to an increase of cement working life and activity. Concrete samples have been obtained that have improved physico-mechanical properties owing to introduction the following components in their composition: 2–14 % (of cement mass) of ash left after brown coal burning and 1.6–2.1 % of sodium salt that is a condensation product of sulfur oxidate in aromatic hydrocarbons with formaldehyde. Efficiency of the executed work has been proved by solution of the problems pertaining to an increase of neat cement working life, cement activity, concrete strength. The paper also considers no less important problem concerning protection of the environment from contamination with ash left after burning of high-ash brown coal.